Transparency Mechanisms and Non-Tariff Measures Case Studies - Moïsé, Evdokia (OECD Trade Policy Papers, 2011)
Lack of regulatory transparency is a major and recurrent obstacle for businesses seeking to trade internationally. This study finds that transparency mechanisms applied at different stages of the design, finalisation and implementation of domestic regulation have allowed countries to reduce administrative burdens, generate savings both for the administration and for the private sector and maintain a relation of confidence conducive to a smoother enforcement of related policies. They have also helped them enhance the readability of laws and regulations and the predictability of their enforcement (thus further reducing indirect business costs), and prevent potential frictions with trading partners. The resulting improvements in terms of potential business costs can strongly influence the attractiveness of the country for foreign investors